Pilot scale testing of biofilter post-treatment of MIEX treated water - Zappia, L.; Warton, Benjamin; Alessandrino, Michael; Scott, D.; Wylie, J.; Heitz, Anna; Hiller, B.; Masters, D.; Nolan, P.; Thiel, P.; Kagi, Robert; Joll, Cynthia; et al. (IWA Publishing, 2007)
The MIEX (c) (Magnetic Ion Exchange) process, which employs an anion exchange resin for removal of dissolved organic carbon (DOC), was introduced at the Wanneroo Groundwater Treatment Plant in Western Australia in 2001. In this pilot-scale study we examined a range of operational parameters for optimisation of biofiltration of MIEX (R)-clarified waterl. Granular Activated Carbon (GAC) outperformed anthracite as a filter medium. Increasing the empty bed contact time (EBCT) from 8 to 16 minutes improved performance. The GAC biofilters removed up to 20% of DOC and up to 25% of Biodegradable Dissolved Organic Carbon (BDOC), once they had stabilised in biological mode. Chlorine demand was reduced by 51 to 55% and trihalomethane formation potential (THMFP) was reduced by 35 to 50% in GAC biofilter effluent waters at 16 minutes EBCT when compared with their MIEX (R)-treated influent water. GAC biofilters developed more biomass on the surface than anthracite biofilters and this was associated with the greatest BDOC and DOC removals. Interestingly, neither biofilters developed populations of protozoans. Use of chlorinated influent water severely restricted biomass development in all biofilters at surface. Biofilter treatment of chlorinated influent water resulted in the poorest removal of Assimilable Organic Carbon (AOC). Biofiltration improved the water quality of MIEX (R)-clarified waters.